Effect of Dexamethasone in Neospora Caninum Seropositive Calves - Idarraga Bedoya, S. (2020)
The aim of this study was to evaluate the effect of Dexamethasone (DXM) on clinical parameters, absolute and differential leukocyte count, specific IgG titers, IFN-γ production and parasitemia in beef calves seropositive to Neospora caninum. Fifteen calves were assigned to four experimental groups as follow: group A: 4 sero- positive calves treated with DXM; group B: 4 seropositive calves without DXM; group C: 3 seronegative calves treated with DXM, and group D: 4 seronegative calves without DXM treatment. The absolute leukocyte count was higher in both groups A and C in the 3rd day after the first dose of DXM mainly due to a significant neutrophilia (p<0.05). No changes in the total specific IgG titers or ratios between their subisotypes or antibodies against NcGRA7 and NcSAG4 antigens were observed in calves from group A com- pared with those in group B (p>0.05). Similarly, IFN-γ levels did not change among experimental groups (p>0.05). DNA was de- tected in calves from groups A and B at 7 Days Post Administra- tion (dpa) and from group A at 14 dpa. Even when DXM adminis- tration induced hemotological parameter changes, no reactivation of Neospora-infection was observed according to specific IgG titers and presence of the parasite on leukocytes in naturally seropositive beef male calves.